2017
DOI: 10.12659/msm.905136
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Plantar Loads During Walking in Patients with Knee Osteoarthritis

Abstract: BackgroundKnee osteoarthritis (KOA) is a common disease that can change the load on lower limbs during walking. Plantar loads in patients with KOA may provide a basis for clinical decisions regarding footwear and foot orthoses. This study aimed to compare plantar loads in females with and without KOA during gait.Material/MethodsPlantar pressure during walking was recorded in 23 females with KOA and 23 females without KOA. Maximum force (MF), contact area (CA), and peak pressure (PP) were measured at 7 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…In KOA groups, four studies reported a BMI mean of 18.5–24.9 kg/m 2 (normal weight) [ 20 , 28 , 43 , 56 ]; 19 studies reported participants’ mean BMI of 25–29.9 kg/m 2 (overweight) [ 22 , 23 , 27 , 30 , 31 , 33 35 , 38 42 , 44 , 45 , 49 , 52 , 53 , 55 ]; eight studies reported the mean BMI of 30–34.9 kg/m 2 (grade I obese) [ 18 , 21 , 24 26 , 32 , 37 , 48 ]; and one study reported a mean BMI ≥35 kg/m 2 [ 51 ] (grade II obese). Seven studies did not report the mean BMI of their participants [ 19 , 29 , 36 , 46 , 47 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In KOA groups, four studies reported a BMI mean of 18.5–24.9 kg/m 2 (normal weight) [ 20 , 28 , 43 , 56 ]; 19 studies reported participants’ mean BMI of 25–29.9 kg/m 2 (overweight) [ 22 , 23 , 27 , 30 , 31 , 33 35 , 38 42 , 44 , 45 , 49 , 52 , 53 , 55 ]; eight studies reported the mean BMI of 30–34.9 kg/m 2 (grade I obese) [ 18 , 21 , 24 26 , 32 , 37 , 48 ]; and one study reported a mean BMI ≥35 kg/m 2 [ 51 ] (grade II obese). Seven studies did not report the mean BMI of their participants [ 19 , 29 , 36 , 46 , 47 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study [88], also involving patients with knee OA, measured the plantar pressure during walking, as a basis for deciding which footwear and foot orthoses to choose. Three parameters were measured: PP (peak pressure), MaF (maximum force), and CA (contact area), in seven regions underneath the foot: heel, midfoot, first metatarsophalangeal joint (MPJ), second MPJ, third to fifth MPJ, hallux, and lesser toes, respectively.…”
Section: Pedar In Medical Applicationsmentioning
confidence: 99%
“…Uritani et al 19 also demonstrated that women with KOA have less plantar grip strength, a deficit which may contribute to changes in the kinetic chain of the lower limb during gait. 20 From a kinetic perspective, the external knee adductor moment (EKAM), a variable related to the internal loads of the joint, mainly in the medial compartment, was found to be directly and positively associated with pain intensity 21 and KOA progression. 22 Previous studies showed increased peak EKAM in several gait phases in KOA patients compared with asymptomatic subjects.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%